2022
DOI: 10.1007/s44195-022-00004-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of assimilating Formosat-7/COSMIC-II GNSS radio occultation data on heavy rainfall prediction in Taiwan

Abstract: This study investigates the impact of assimilating Formosat-7/COSMIC-II (FS7/C2) radio occultation (RO) refractivity data on predicting the heavy rainfall event that occurred in Taiwan on August 13, 2019. This event was characterized by heavy rainfall over the coastal region of central and southwestern Taiwan. Our investigation is performed using the Weather Research and Forecasting-Local Ensemble Transform Kalman Filter. Generally, assimilating the RO data increases the amount of moisture over the northern So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Existe uma vasta gama de investigações que ainda se faz necessária nessa área de pesquisa, não apenas em relação às novas missões, mas também quanto às configurações de processamento, metodologias envolvidas na obtenção e validação dos perfis atmosféricos e, ainda, as metodologias de assimilação dos dados de RO-GNSS em modelos atmosféricos. Diversos estudos recentes apresentam importantes contribuições em relação à atmosfera neutra (ANTHES et al, 2022;FU et al, 2022;YANG, 2022) e à ionosfera (BERGSSON;SYNDERGAARD, 2022;SUN et al, 2022;PROL et al, 2022).…”
Section: Considerações Finaisunclassified
“…Existe uma vasta gama de investigações que ainda se faz necessária nessa área de pesquisa, não apenas em relação às novas missões, mas também quanto às configurações de processamento, metodologias envolvidas na obtenção e validação dos perfis atmosféricos e, ainda, as metodologias de assimilação dos dados de RO-GNSS em modelos atmosféricos. Diversos estudos recentes apresentam importantes contribuições em relação à atmosfera neutra (ANTHES et al, 2022;FU et al, 2022;YANG, 2022) e à ionosfera (BERGSSON;SYNDERGAARD, 2022;SUN et al, 2022;PROL et al, 2022).…”
Section: Considerações Finaisunclassified
“…The RO data with a nonlocal operator contributes to a remarkable improvement in typhoon track prediction through Typhoon Hagupit's (2020) and Haishen's (2020) case studies. Chang and Yang (2022) [38] also assimilated FS7 refractivity but used the WRF local ensemble transform Kalman filter (WRF-LETKF) hybrid DA system. As expected, assimilating with FS7 RO data would improve low-level moisture analysis; however, they found that excluding the RO data below 3 km facilitated better rainfall prediction.…”
Section: Anthes Et Al (2021)mentioning
confidence: 99%
“…After FS7 was launched, the data quality was verified by comparing it with other independent data, such as radiosondes, model forecasts, and reanalyses [27][28][29][30][31][32][33][34][35][36][37][38]. As the first summary of the initial FS7 quality assessment, Schreiner et al (2020) [27] confirmed that FS7 RO data meet expectations of high accuracy and precision.…”
Section: Introductionmentioning
confidence: 98%
“…Schreiner et al (2020) identified that the low-level negative biases still exist in the FS7-C2 RO data. Chang and Yang (2022) showed that a heavy rainfall event caused by the long-range moisture transport from southern China and South China Sea can be better predicted when the FS7-C2 RO data above 3 km are assimilated.…”
Section: Introductionmentioning
confidence: 99%